Pengaruh Aplikasi Biochar Sekam Padi Dan Umur Panen Terhadap Hasil Ubi Jalar Naruto Kintoki Pada Tanah Podsolik Merah Kuning - Julianto, Bayu; Supriyanto, Supriyanto; Pramulya, Muhammad (Fakultas Pertanian Universitas Tanjungpura, 2025)
Naruto Kintoki sweet potato (Ipomoea batatas L.) is a superior variety valued for its sweet taste and soft texture, but its cultivation in Indonesia remains limited. This study aimed to examine the interaction between rice husk biochar application and harvest age on the yield of Naruto Kintoki grown in ultisol soil. The research was conducted in the Pontianak Kota District, from September 2024 to February 2025. A factorial Completely Randomized Design (CRD) was used with two factors: biochar (2, 4, and 6 tons/ha) and harvest age (90, 105, and 120 days). Results showed significant interaction effects on growth and yield. A harvest age of 120 days with 4 tons/ha biochar produced the longest main vine (176.79 cm) and the largest tuber diameter (55.28 mm). The highest tuber number (4.60) and tuber weight (447.51 g) were found with 120 days and 6 tons/ha biochar. This study contributes to scientific knowledge by demonstrating how biochar and harvest timing influence both yield and tuber quality. It supports the sustainable cultivation of Naruto Kintoki in acidic, nutrient-poor ultisol soils and provides a model for optimizing sweet potato production on marginal tropical lands.